Блок детектирования гамма-излучения на основе CdZnTe для систем радиационного контроля - Mokritsky, V. A.; Maslov, O. V.; Nikolaenko, Yu. E.; Maksimov, M. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The use of CdZnTe for dose rate measurement is limited by the fact that the detector’s sensitivity varies by a factor of more than 10 in the γ-ray energy range of 10 keV to 3 MeV. To reduce the error caused by the detector sensitivity’s dependence on gamma-ray energy, digital correction of the output signal is used. The correction is performed by varying the pulse frequency at the output of the detection unit depending on the gamma-ray energy. A piecewise-linear linearization of the dependence of the count rate change coefficient on energy is applied.